Analisis Kompetensi Sumber Daya Manusia (SDM) Kinerja Pegawai Pada Kantor Dinas Komunikasi dan Informatka Kabupaten Karawang - Rahayu, Rizky Eva; Sungkono, Sungkono; Retnosary, Rieke (Peneliti.net, 2024)
This research aims to look at human resource competency in the performance of employees in the Karawang Regency Communication and Information Service and provide suggestions and input to be used as a work evaluation by the agency. The analytical method used in this research is a qualitative descriptive method, that is, based on facts found in the field, then used as a hypothesis or theory to obtain in-depth data (actual and certain data). This research was carried out using data collection methods by observation and interviews with related parties. The data analysis method used is qualitative analysis using the interactive analysis model from Miles and Huberman which is divided into 4 major parts, namely data collection, data reduction, data presentation, drawing conclusions and verification. The results of the research show that the performance of Communication and Information Service employees does not yet have procedures that regulate human resource planning, so that employees have not carried out job descriptions in accordance with their respective competencies. Therefore, it is necessary to plan higher quality human resources by prospectively conducting employees so that they are able to create competencies according to work needs.